ANALYSIS OF BIOMASS AND CARBON RESERVES IN THE SOUTH PART OF RUPAT ISLAND MANGROVE ECOSYSTEM - Eddy Handoko; Bintal Amin; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in December 2015-February 2016 on mangrove ecosystems in the coastal area of South part of Rupat Island, Riau Province. The aim of research was to analyze the content of biomass and carbon in mangrove ecosystems as well as the ability to store carbon in the forest area. The survey method was applied in this research and carbon analysis was carried out in the Marine Chemistry Laboratory of Faculty of Fisheries and Marine Science of University of Riau. The results showed that the potential mangrove biomass was directly proportional to mangrove carbon stocks. The average yield of carbon stocks of biomass and organic carbon reserves of soil amounted to 58.8 tons/ha and 920.12 tons/ha, while the average yield of total carbon stocks was 978,92 tons/ha.Keyword : Mangrove, Biomass, Carbon Stocks, Rupat Island1)